THE IMPACT OF POVERTY ON ECONOMIC GROWTH FROM AN ISLAMIC PERSPECTIVE - Nur Alfi Laili; Laila Musfiroh (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Abstract: Growth is an important requirement to combat poverty as a condition for growth, it is enough to provide an effective contribution to reducing poverty. This study aims to understand the extent to which poverty is affected by the Covid-19 pandemic, this will cause an increase in poverty rates in Indonesia and affect the rate of economic growth, this study is a qualitative study using a descriptive approach method. And the method of data collection uses the library survey method. Through this study, it is expected to reduce the level of poverty and thus have an impact on the level of economic growth, with economic growth being a factor in the success of economic developmen. Keywords: poverty rate, economic growth, real impact of economic growth against poverty